Estimating Combining Ability Effect of the Indian and Exotic Lines of Tomatoes by Partial Diallel Analysis - Suresh Baban Dagade; Nanadasana Jagdish Nasibhai; Hariprasanna Krishna; Bhatt Virendra Mulshankar; Dhaduk Lallubhai Keshavbhai; Barad Agarsang Virsanbhai (Turkish Journal of Agriculture: Food Science and Technology)
Eight nearly homozygous, horticulturally superior and optimally divergent lines of tomato having Indian and exotic adaptability were used for carrying out half diallel design to study General Combining Ability (GCA) and Specific Combining Ability (SCA) estimates for fruit weight, polar and equatorial diameter, locules fruit-1, pericarp thickness and fruit firmness. The variances due to both GCA and SCA were significant, suggesting that both additive and non additive genetic variance were involved for genetic control of the character fruit polar and equatorial diameter, and locules number in F1 and F2 generations. However, the variance due to GCA was more pronounced for fruit weight, pericarp thickness and firmness as a result of additive gene action. Due to their high general combining ability effects, exotic parents Ec 490130 and Ec 177371 producing firm fruited small to medium sized tomato fruits having constant expression of GCA effects over the generationsregarded as best general combiners. The crosses GT 1 x Ec 490130 and Ec 490130 x Ec 398704 having high x high and high x low combinations, respectively in F1. While in F2, GT 1 x Ec 177371 and H 24 x Ec 490130 having high x high and high x low combining lines were considered as best crosses for greater fruit firmness. Therefore, heterosis breeding in F1 and selection of desirable lines in F2 generation is recommended for further improvements were suggested for future hybridization programmes.